Implementation of a workplace physical activity intervention in child care: process evaluation results from the Care2BWell trial. Issue 7 (17th April 2021) - Neshteruk, Cody D; Willis, Erik; Smith, Falon; Vaughn, Amber E; Grummon, Anna H; Vu, Maihan B; Ward, Dianne S; Linnan, Laura
Abstract: Care2BWell was designed to evaluate the efficacy of Healthy Lifestyles (HL), a worksite health promotion intervention to increase child care workers' physical activity. The purpose of this study was to use process evaluation to describe the implementation of HL and determine if different levels of implementation are associated with changes in workers' physical activity. Data were collected from 250 workers randomized to HL, a 6 month, multilevel intervention that included an educational workshop followed by three 8 week campaigns that included self-monitoring and feedback, raffle incentive, social support, and center director coaching. Process evaluation data collection included direct observation, self-reported evaluation surveys, website analytics and user test account data, tracking databases and semi-structured interviews. Implementation scores were calculated for each intervention component and compared at the center and individual levels. Nearly a third of workers never self-monitored and few (16%) met self-monitoring goals. Only 39% of centers engaged with the social support component as intended. Raffle and social support components were perceived as the least useful. Implementation varied widely by center (25%–76%) and individual workers (0%–94%). No within- or between-group differences for high compared to low implementation groups for change in physical activity were evident. Interview themes included limited sustainability, competing priorities, importance of social support, and desire for a more intensive, personalized intervention. Wide variation in implementation may explain limited effects on intervention outcomes. Future worksite interventions designed for child care workers can use these findings to optimize health promotion in this setting.